As missivas de Jane Vanini e as disputas pela memória - Amaro, Kátia Gomes da Silva (2012)
This research aims to study the relationship between the trajectory of a militant leftist political refugee, and later murdered by the Chilean military regime and the context of repression underway in Latin America. A significant part of the documentary corpus used in this research is to thread the letters written by Jane Vanini when it lived drama of hiding in Chile from 1972 to 1974. This research seeks to think Jane Vanini, not only as a character to "explain everything" or group of militancy, it is therefore submitting its singularity, imposing itself between the paths of the Brazilian dictatorship period and the constitution of the Chilean dictatorship, gaps those created by herself, through the practice clerk of his letters, when militancy was assumed that political engagement dismissing those of private life, forcing them to "erase" their tracks. Research will present the ongoing tensions between aspects of a public nature linked to militancy Jane Vanini in the People's Liberation Movement-MOLIPO when I was in Brazil and later in the Isquierda Movimiento Revolucionario (MIR) when exiled with her first husband in Chile and a private dimension of his life and colloquial. The same analysis is possible to find references where the author of the letters, distant relatives of these themes, evidenced an effort to establish a strong image of young guerrilla engaged in a project to transform the world struggling in the constitution of identity by which it was known in Chile, which is that of the militant Gabriela, who in his letters strove to convince his family of the adequacy and necessity of your choice, always based on a rigorous analysis of the world.